Efektivitas Media Kartu Kata Bergambar dalam Meningkatkan Minat Baca Anak di TK Al-Jamiatul Amaliyah Gerumpung Desa Sepit: The Effectiveness of Picture Word Card Media in Increasing Children's Reading Interest at Al-Jamiatul Amaliyah Gerumpung Kindergarten, Sepit Village - Syarifatul Munawarah; Yuliana Susanti; Aslamiah, Suhaibatul (Pendidikan Al-Gafari, 2025)
Education has the most important position in improving human resources. Through education, it is expected that individuals have competence so that they can compete with others. The objectives to be achieved in this study are: 1) To determine the process of implementing picture card media in increasing children's reading interest in TK Al-Jam'iyatul Amaliyah Gerumpung, Sepit Village. 2) To determine how effective the picture card media is in increasing children's reading interest in TK Al-Jam'iyatul Amaliyah Gerumpung, Sepit Village. The research method used is descriptive qualitative with a survey research design. This research was conducted at TK Al-Jam'iyatul Amaliyah Gerumpung, Sepit Village, Keruak District, East Lombok, West Nusa Tenggara. In this study, the researcher used three data collection techniques, namely observation, interviews and documentation. The data analysis technique that has been used is descriptive analysis technique with data reduction, data presentation, and verification components. The results of the study indicate that the process of implementing Picture Card Media in increasing children's reading interest in TK Al-Jam'iyatul Amaliyah Gerumpung Desa Sepit is through the following stages: 1) introduction and preparation; 2) integration in learning activities; 3) content adjustment; 4) stimulation of reading interest; 5) increasing vocabulary; 6) increasing self-confidence; 7) measurement and evaluation; 8) feedback from students; 9) further development; and 10) conclusions and reflections. This study also shows that Picture Card Media has a positive impact on increasing children's reading interest in TK Al-Jamiatul Amaliyah Gerumpung Desa Sepit. This is evident from 5 teacher respondents out of 6 teachers in the kindergarten who have a positive view of 83.33%, and from a total of 20 students who participated, there were 14 students who had a positive response of 70%. And proven by the 15 number of parents who participated in this study, there were 12 respondents 80% who had a positive view.